(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This research is based on the background of Kuda Kosong art in Cianjur Regency, which was once banned and reappeared. There still needs to be more writings and studies on the local history of Kuda Kosong in Cianjur Regency. This research focuses on developing Kuda Kosong art in Cianjur Regency from 1998 to 2011. This research aims to obtain information about the ups and downs of Kuda Kosong art in the Cianjur Regency. This research aims to obtain information about the ups and downs of Kuda Kosong art in Cianjur Regency. The method used in this research is the historical method, consisting of several steps that include the collection of source materials, verification or criticism of research sources, and historiography or written history. The results of the Kuda Kosong art research in Cianjur Regency contain information that this art has existed since the 18th century in Cianjur Regency. The development of Kuda Konsong art experienced ups and downs, and there were changes in function. Kuda Kosong art can be presented openly, which pavilion guests can only witness. The procession of ngalinggihkeun and ngalungsursur in Kuda Kosong art is abolished because it does not follow Islamic law. As a result, it hindered the development of Kuda Kosong art in 1998. To preserve Kuda Kosong art, the government cooperated with various parties involved, namely artists, culturalists, and MUI, so that Kuda Kosong art could be staged again, provided some deviant processions are omitted.